2015
DOI: 10.1039/c5ce00903k
|View full text |Cite
|
Sign up to set email alerts
|

A series of entangled coordination polymers assembled by a V-shaped bisimidazole ligand and various dicarboxylic acids: synthesis, characterization and luminescence properties

Abstract: Based on a V-shaped bisimidazole ligand and various dicarboxylic acids, nine entangled coordination polymers, namely, ijZnIJo-bdc)IJbips)]·2H 2 O (1), ijZn 2 IJcdc) 2 IJbips) 2 ]·2H 2 O (2), ijZn 2 IJbpedc) 2 IJbips) 2 ] (3), ijZnIJodc)IJbips)] ·H 2 O (4), ijZn 2 IJsdc) 2 IJbips) 2 ]·5H 2 O (5), ijCo 2 IJsdc) 2 IJbips) 2 IJH 2 O)]·2H 2 O (6), ijCd 2 IJbpdc) 2 IJbips) 2 ]·3H 2 O (7), ijCd 2 IJ2,6ndc) 2 IJbips) 2 IJH 2 O) 2 ]·2H 2 O (8) and ijCdIJ1,4-ndc)IJbips)]·DMF·H 2 O (9) (bips = bisIJ4-imidazol-ylphenyl)sulfone, o-H 2 bdc = o-phenyldic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…For such a purpose, a fluorescent linker such as 2,6-H 2 NDC has been introduced for two reasons: (i) to help in the formation of diversified structure due to the presence of a planar naphthalene moiety between two carboxylates oriented at an angle of 180° which is similar to that for H 2 adc but with an aromatic ring and (ii) to have sensing applications due to its fluorogenic nature. In addition to the compounds with 2,6-NDC mentioned above, , several other compounds with 2,6-NDC have been reported in the literature but not utilized for sensing applications …”
Section: Introductionmentioning
confidence: 99%
“…For such a purpose, a fluorescent linker such as 2,6-H 2 NDC has been introduced for two reasons: (i) to help in the formation of diversified structure due to the presence of a planar naphthalene moiety between two carboxylates oriented at an angle of 180° which is similar to that for H 2 adc but with an aromatic ring and (ii) to have sensing applications due to its fluorogenic nature. In addition to the compounds with 2,6-NDC mentioned above, , several other compounds with 2,6-NDC have been reported in the literature but not utilized for sensing applications …”
Section: Introductionmentioning
confidence: 99%
“…One of the complexes prepared in [84] utilizes H 2 sdc as co-ligand for building of the Zn 2+ based framework.…”
Section: Coordination Polymers Based On 44 -Stilbenedicarboxylic Acidmentioning
confidence: 99%
“…[16][17][18] Through literature research, we found that 4,4'-dicarboxybiphenyl sulfone (H 2 SDBA) as a Vshaped dicarboxylate ligand is an good candidate and has been widely employed as the organic building block for the construction of novel coordination frameworks independently or in combination with N-donor auxiliary ligands. [19][20][21][22][23] (2) and [Cu(SDBA) 0.5 (μ 2 -OH)] n (3) (H 2 SDBA=4,4'-dicarboxybiphenyl sulfone, im = imidazole, DMA = N,N'-dimethylacetamide). The structures of CPs 1-3 have been described, and the luminescent properties of 1-2, gas adsorption properties of 2 a (solvent-free form of 2) and photocatalytic property of 3 have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Among the reported CPs, polydentate organic carboxylic acid ligands have been proven to be one of the most effective organic building blocks to bind metal ions into well‐defined crystalline functional materials, [13–15] and lots of CPs with high thermal stabilities and promising functional properties have been synthesized by using the polycarboxylate ligands [16–18] . Through literature research, we found that 4,4’‐dicarboxybiphenyl sulfone (H 2 SDBA) as a V‐shaped dicarboxylate ligand is an good candidate and has been widely employed as the organic building block for the construction of novel coordination frameworks independently or in combination with N‐donor auxiliary ligands [19–23] . The characteristics of H 2 SDBA is the appropriate angle and spacer length between two coordination carboxylate groups.…”
Section: Introductionmentioning
confidence: 99%